A systematic study of the competitive sorption of per- and polyfluoroalkyl substances (PFAS) on colloidal activated carbon - Georgios Niarchos; Linnea Georgii; Lutz Ahrens; Dan Berggren Kleja; Fritjof Fagerlund (Ecotoxicology and Environmental Safety, 2023)
Treatment of environmental media contaminated with per- and polyfluoroalkyl substances (PFAS) is crucial to mitigate mounting health risks associated with exposure. Colloidal activated carbon (CAC) has shown promise in treating contaminated soils, but understanding the interaction among PFAS during sorption is necessary for optimal remediation. This study investigated the extent to which PFAS of varying chain lengths and functional groups compete for sorption to CAC. Batch tests were conducted with natural soil and spiked water, using CAC at 0.2% w/w to remove seven PFAS with individual starting concentrations up to 0.05 mmol L−1. PFAS sorption to CAC was evaluated in three systems: a composite mixture of all studied compounds, a binary-solute system, and a single-solute system. The sorption experiments exhibited strong PFAS affinity to CAC, with removal rates between 41% and 100%, and solid/liquid partition coefficients (Kd) between 10 and 104 L kg−1. Differences were noticed among the various spiking mixtures, based on perfluorocarbon chain length, functional group, and the starting PFAS concentrations. Competition effects were detected when PFAS were in a multi-solute system, with an average 10% drop in removal, which can evidently become more relevant at higher concentrations, due to the observed non-linearity of the sorption process. The PFAS most vulnerable to competition effects in multi-solute systems were the short-chain perfluoropentanoic acid (PFPeA) and perfluorobutane sulfonic acid (PFBS), with an up to 25% reduction in removal. In bi-solute systems, perfluorooctane sulfonamide (FOSA) dominated over its ionisable counterparts, i.e. perfluorooctane sulfonic acid (PFOS) and perfluorononanoic acid (PFNA), indicating the importance of hydrophobic effects or layer formation in the sorption process. These results underscore the importance of considering competition in PFAS sorption processes when designing and implementing remediation techniques for PFAS-contaminated media.